2018
DOI: 10.1101/405035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-cancer pleiotropic associations with lung cancer risk in African Americans

Abstract: Background:Identifying genetic variants with pleiotropic associations across multiple cancers can reveal shared biologic pathways. Prior pleiotropic studies have primarily focused on European descent individuals. Yet population-specific genetic variation can occur and potential pleiotropic associations among diverse racial/ethnic populations could be missed. We examined crosscancer pleiotropic associations with lung cancer risk in African Americans. Methods:We conducted a pleiotropic analysis among 1,410 Afric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…For example, DHODH G202A, R346W causes deficient protein stability and R135C impairs the enzymatic activity, which are linked to Miller syndrome 10 , 11 . DHODH polymorphism was reported to be linked with rheumatoid arthritis and lung cancer as well 12 14 . Additionally, enhanced activity of DHODH has been implicated as a biomarker of malignant tumor including gastric cancer and skin cancer 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, DHODH G202A, R346W causes deficient protein stability and R135C impairs the enzymatic activity, which are linked to Miller syndrome 10 , 11 . DHODH polymorphism was reported to be linked with rheumatoid arthritis and lung cancer as well 12 14 . Additionally, enhanced activity of DHODH has been implicated as a biomarker of malignant tumor including gastric cancer and skin cancer 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) of individual cancers have identified loci associated with multiple cancer types, including 1q32 (MDM4) 7,8 ; 2q33 (CASP8-ALS2CR12) 9,10 ; 3q28 (TP63) 11,12 ; 4q24 (TET2) 13,14 ; 5p15 (TERT-CLPTM1L) 9,12 ; 6p21 (HLA complex) 15,16 ; 7p15 17 ; 8q24 12,18 ; 11q13 18,19 ; 17q12 (HNF1B) 18,20 ; and 19q13 (MERIT40) 21 . In addition, recent studies have tested single-nucleotide polymorphisms (SNPs) previously associated with one cancer to discover pleiotropic associations with other cancer types [22][23][24][25] . Consortia, such as the Genetic Associations and Mechanisms in Oncology, have looked for variants and pathways shared by breast, colorectal, lung, ovarian, and prostate cancers [26][27][28][29][30] .…”
mentioning
confidence: 99%
“…The present study was based on 35 SNPs that can potentially modify the risk of cancer. A literature research revealed that only 10 of these 35 SNPs were described in studies of African or Afro-American populations (Mechanic et al, 2007;Chornokur et al, 2013a;Nikolić et al, 2014;Oh et al, 2017a;Oussalah et al, 2017;Tong et al, 2018;Jones et al, 2019;Sagna et al, 2019;Song et al, 2019;Kamiza et al, 2020), suggesting that most association studies including these SNPs focused on European and Asian populations. The present results showed that a high number of individuals were homozygous for risk alleles with Native American and African ancestry that may modify the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%